Effect of topical phenytoin with normal saline dressing in patients of diabetic foot ulcers - Srinivas Reddy, Manohar; Reddy Jagadish Madinur, Chandrashekar (International Surgery Journal, 2021)
Background: The management of wound and wound dressing is an important aspect of chronic ulcer management. Choosing an appropriate dressing can be a complex process. Topical phenytoin helps in faster wound remodelling. The objective of the study was to assess the effect of topical phenytoin dressing with normal saline dressing in healing of diabetic foot ulcer in terms of mean decrease in size of the ulcer. Methods: The present study was conducted on 60 patients with diabetic foot ulcer. The patients were divided into two different groups (group 1 topical phenytoin and group 2 normal saline dressing). Wound measurement was taken on day one and end of every week for four weeks. Mean reduction in ulcer area at the end of four weeks was calculated. Results: There was no statistical difference in the baseline characteristics like age, sex and initial wound area of the ulcer between the two groups. The mean reduction in wound area was 1856.9±724.9 mm2 in patients treated with topical phenytoin dressings and 1066.8±565.3 mm2 in patients treated with normal saline dressings, which is statically significant (p<0.001). Conclusions: The study concluded that the topical phenytoin dressing can be used for the healing of diabetic foot ulcer.